PRELIMINARY INVESTIGATION INTO SOME ASPECTS OF THE ECOLOGY OF COASTAL SAVANNAH FOREST SOILS IN GHANA: A Case Study of the University of Cape Coast Nature Reserve (Journal of Science and Technology, 2016)
The study was conducted in the University of Cape Coast Nature Reserve to investigate the levels of urease in the soils and to relate these levels to soil organic matter (SOM) content, soil moisture (SM) content, pH, temperature, particle size distribution and bulk density. The stratified random sampling method was employed to collect data within three 10 × 200 m belt transects. Soil samples were collected from 0 to 15 cm depth in different zones of the nature reserve between January and April, 2005. The mean soil urease levels ranged from 80.91 ± 4.72 to 132.36 ± 10.80 NH4+-N mg kg-1. Monthly variations in soil urease levels were highly significant (p < 0.01). The enzyme level varied significantly (p < 0.001) with topography. Multiple regression analysis showed that urease activity depended on SOM, SM, pH and soil temperature (p < 0.05). Soil texture and bulk density were similar in all the zones. SOM, SM, time and topography were the main factors which affected urease levels in the soils of the University of Cape Coast Nature Reserve.